1985
DOI: 10.1148/radiology.157.3.3864189
|View full text |Cite
|
Sign up to set email alerts
|

Invasive pulmonary aspergillosis in acute leukemia: characteristic findings on CT, the CT halo sign, and the role of CT in early diagnosis.

Abstract: Invasive pulmonary aspergillosis (IPA) in immunocompromised patients is often difficult to diagnose. Many pathogens present initially with similar, nonspecific pulmonary findings. Air crescent formation has been reported to be highly suggestive of IPA in the appropriate clinical setting, but this is a late sign in an otherwise rapidly fatal infection. The authors reviewed the available chest computed tomography (CT) scans of nine patients with acute leukemia and documented IPA, including four patients with ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
169
3
13

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 419 publications
(193 citation statements)
references
References 0 publications
8
169
3
13
Order By: Relevance
“…This finding is different from those of Kuhlman et al (11) , whose percentages were respectively 55% and 22%. Cavitation was found in only one of our cases of mass (25%), while Kuhlman et al (4) observed percentages of up to 71%.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…This finding is different from those of Kuhlman et al (11) , whose percentages were respectively 55% and 22%. Cavitation was found in only one of our cases of mass (25%), while Kuhlman et al (4) observed percentages of up to 71%.…”
Section: Discussioncontrasting
confidence: 98%
“…Consolidations were predominantly peripheral in 83.3% in this casuistic, while in the great majority of studies in the literature these percentages have reached approximately 100%. In our study, consolidations were multiple in 66.6% of cases which is in agreement with authors like Kuhlman et al (11) and Won et al (19) .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…14). Initial wurde es bei der invasiven pulmonalen Aspergillose als Manifestation perifokaler Hämorrhagien beschrieben [21], es ist jedoch unspezifisch und kommt auch bei Hämorrhagien anderer Ursache [22] wobei die Basis der Pleura anliegt und die Spitze in Richtung des Hilus gerichtet ist [23,24]. Die radiologisch sichtbaren Verände-rungen entsprechen überwiegend pulmonalen Hämorrhagien infolge des Infarkts, eventuell auch einer Nekrose.…”
Section: Halozeichenunclassified